THE DIFFERENCE OF THE DECREASE BLOOD SUGAR LEVEL THROUGH AEROBIC EXERCISE AND RESISTANCE EXERCISE IN PREDIABETES PATIENTS - Wulandari, Enny; Sundari, Luh Putu Ratna; Lesmana, Indra; Adiatmika, I Putu Gede; Adiputra, Luh Made Indah Sri Handari; Muliarta, I Made (Sport and Fitness Journal; Vol 10 No 1 (2022): Volume 10, No. 1, January 2022, 2022)
Prediabetic is a situation where the person’s blood sugar level is above normal but has not fully categorized as Diabetes Mellitus. The decrease of blood sugar level in prediabetes patients can be done in various methods, such as Aerobic Exercise and Resistance Exercise . This study aims to investigate the difference of the decrease blood sugar level through Aerobic Exercise and Resistance Exercise in prediabetes patients. Experimental with pre test and post test two group design is used in this study. It was conducted in Tonja sub-distict, North Denpasar in January until March 2020. The research sample is 24 people, where 21 is woman and 3 man which are randomly divided into 2 experimental groups. Experimental Group I was given Aerobic Exercise and experimental group II was given Resistance Exercise. Glucometer is used as a measurement tool in this study. Based on the result of paired t-test , there is a decrease in blood sugar level in Experimental Group I, which the average before intervention is 146,58±21,33mg/dL into 126,42±21,03mg/dL after intervention and obtained p=0,001(<0,05). In Experimental Group II, the blood sugar level is decreased, where the average before intervention is 142,33±16,71mg/dL and after intervention is 121,83±20,83mg/dL and p=0,001(<0,05). There is no significant difference in the decrease of blood sugar level between two groups with p=0,948(>0,05). The conclusion is both Aerobic Exercise and Resistance Exercise have a good effect in decreasing blood sugar level. Keywords: Aerobic Exercise; Resistance Exercise; Prediabetes; Blood Sugar